PENGARUH UKURAN PERUSAHAAN, KOMISARIS INDEPENDEN DAN INTENSITAS ASET TETAP TERHADAP MANAJEMEN PAJAK - Agustin, Nanda; Yusuf, Nur’aini (Publika Citra Media, 2025)
This study aims to analyze and provide empirical evidence on the effect of firm size, independent commissioners, and fixed asset intensity on tax management. This type of research is associative quantitative, utilizing secondary data in the form of annual financial reports of banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period from 2019 - 2023. The sampling procedure used in this study was purposive sampling, resulting in 19 companies that met the criteria. The variables used in this study include firm size as the first independent variable, independent commissioners as the second independent variable, and fixed asset intensity as the third independent variable, with tax management as the dependent variable. The analysis technique applied was panel data regression analysis using the E-views 12 software. The results of this study indicate that firm size significantly influence tax management, while independent commissioners and fixed asset intensity do not have a significant effect on tax management.